Comparing the Expression of CDX2 & SATB2 in Samples of Iraqi Patients with Colorectal Cancer - Azeez, Rasha Abbas; Al-Jowari, Suha Abdul-Khaliq; Mahmood, Hayder Jamal (Iraqi Journal of Science, 2024)
The purpose of this study was to assess the diagnostic value of the immunohistochemical expression of Special AT-rich sequence binding protein (SATB2) alone and in combination with the caudal type homeobox 2 (CDX2) in colorectal cancers (CRCs) in Iraqi patients. This study's samples collection for tissue and practical work spanned twelve months, 20 December 2021 to 20 December 2022. A total of 80 male and female participants (41 CRC, 19 severe colitis and 20 controls) were examined. For each case, at least two 4-µm-thick tissue sections were cut for immunohistochemical staining with CDX2 and SATB2 immunohistochemical markers. According to the current study results all samples of CRC patients showed positive expression for STAB2 and CDX proteins with significantly higher (p< 0.001) frequencies of expression recorded in score 3, 78.05% and 99.9% respectively, in comparison to other study groups. A positive correlation between the two studied markers was found and both could be used as diagnostic markers for CRC.